(untitled) (Journal of Philosophy Culture and Political Science, 2015)
There is considered mass media of Germany which have the media features, including the sovereignty of federal lands in the field of the press and TV and radio broadcasting or parallel existence of public and private mass media that is not characteristic for all western countries. Concerning freedom of press and a freedom of speech at Germany has also good positions in comparison with other countries. The pluralism of opinions and pluralism of information is provided at rather high level. The press is not in hands of the governments or parties, it is in hands of representatives of society. In Germany representatives of mass media possess big, than someone, rights to collect and distribute information. These rights are a consequence of a special role of media space in formation of public opinion and service to public interests. In Germany the most important element of a freedom of speech and the press is also the pluralism of publications.